2021
DOI: 10.3390/f12030369
|View full text |Cite
|
Sign up to set email alerts
|

Is the Seasonal Variation in Frost Resistance and Plant Performance in Four Oak Species Affected by Changing Temperatures?

Abstract: Research Highlights: We found seasonal variation in frost resistance (FR) and plant performance which were affected by growth temperature. This helps to better understand ecophysiological processes in the light of climate change. Background and Objectives: FR and photosynthesis are important plant characteristics that vary with the season. The aim of this study was to find out whether there is a seasonal variation in FR, photosynthetic CO2 assimilation rates and leaf functional traits associated with performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This shows an intraspecific change associated with a reduction in plant growth that could be related to an increase in resistance (indicated by higher LDMC) and light protection, which is provided by hairs [ 23 , 25 , 26 ]. This can again be a seasonal effect, as species increase LDMC and decrease SLA in autumn if leaves are not shed [ 53 , 54 ]. The increase in hairiness was especially noticeable in harvest 2, which could be due to the fact that they help the plant to insulate against cold temperatures and not just against high irradiation [ 26 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows an intraspecific change associated with a reduction in plant growth that could be related to an increase in resistance (indicated by higher LDMC) and light protection, which is provided by hairs [ 23 , 25 , 26 ]. This can again be a seasonal effect, as species increase LDMC and decrease SLA in autumn if leaves are not shed [ 53 , 54 ]. The increase in hairiness was especially noticeable in harvest 2, which could be due to the fact that they help the plant to insulate against cold temperatures and not just against high irradiation [ 26 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…the fitness of the individual plants was consistent, as was the performance [ 41 , 55 , 56 ]. Previous studies showed a strong decrease in F v /F m and PI abs , with senescence effects at the end of the season [ 53 , 54 , 57 ]. Thus, senescence effects within the remaining plant species can be excluded as driving factor between patterns.…”
Section: Discussionmentioning
confidence: 99%